Techniques for Preparation of Histologics - Turayev Adham Abdulfayiz o’gli; Eshboriyev Javohir Bobomurot o’g’li; Ibragimov Farkhod Bozor o’g’li; Sayfutdinov Samandar Gulomjon o’g’li (Peerian Journals Publishing, 2022)
The main purpose of the article is to study the technique of preparation of histological micropreparations, the structure and operation of light and electron microscopes, that is, the correct use of the microscope to distinguish the structural properties of tissues and cells in drugs, depending on their specific color.
Keywords: preparation; cutting; deparaffinization; washing